2016
DOI: 10.1002/chem.201600901
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Fluorinated Graphene under Heat Treatment

Abstract: Fluorination modifies the electronic properties of graphene, and thus it can be used to provide material with on-demand properties. However, the thermal stability of fluorinated graphene is crucial for any application in electronic devices. Herein, X-ray photoelectron spectroscopy (XPS), temperature-programmed desorption (TPD), and Raman spectroscopy were used to address the impact of the thermal treatment on fluorinated graphene. The annealing, at up to 700 K, caused gradual loss of fluorine and carbon, as wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
2
13
1
Order By: Relevance
“…This direct relationship is further supported by correlation of the median of the I D / I G ratio obtained from Raman maps and the fluorine content measured by XPS (Figure ). Slight deviation of I D / I G from a linear correlation for the annealed sample can be explained by the creation of a significant number of vacancy‐like defects in the graphene layer after annealing …”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This direct relationship is further supported by correlation of the median of the I D / I G ratio obtained from Raman maps and the fluorine content measured by XPS (Figure ). Slight deviation of I D / I G from a linear correlation for the annealed sample can be explained by the creation of a significant number of vacancy‐like defects in the graphene layer after annealing …”
Section: Resultscontrasting
confidence: 99%
“…Because the sample was stored in vacuum without access to humidity, it is likely that previously intercalated water and OH species were responsible for the defluorination process. The reaction of adsorbed hydroxyl groups with fluorine attached to graphene produces HF, which can easily desorb from the surface . Interestingly, the underlying copper crystal structure influenced the stability of fluorinated graphene.…”
Section: Resultsmentioning
confidence: 99%
“…For FGO and FGO−CS, a power‐density‐dependent temperature‐rise behavior was also observed (Figure b), and when the concentration was 0.05 mg mL −1 , the temperature of the suspension reached 45 °C even under a low power of 1.0 W cm −2 . It has been reported that such a temperature can effectively enhance efficacy of drug release and its toxicity toward cancer cells . Moreover, as depicted in Figure c, FGO−CS keeps good photothermal stability even after cycles of on/off irradiation, suggesting enough reliability for practical applications in photothermal therapy or photothermal enhanced drug release or chemotherapy.…”
Section: Resultssupporting
confidence: 73%
“…It is considered that when the conditions are acidic, especially below 5, the amino groups on CS chains are fully protonated and thus the FGOÀCS sheets are individually dispersed in water due to the strong electrostatic repulsion, [45] and the extendedC Sb ranches make the size of FGOÀCS (ca. [46][47][48][49] Moreover,a sd epicted in Figure 4c,F GOÀCS keeps good photothermal stability even after cycles of on/off irradiation, suggesting enoughr eliability for practical applications in photothermalt herapy or photothermal enhanced drug release or chemotherapy. 60 nm).…”
Section: Resultsmentioning
confidence: 93%
“…10 Furthermore, we recently demonstrated how the pulsed laser deposition of ceria nanoparticles on graphene could induce the formation of defects. 11 Another method that leads to local defects is the application of the electron beam in the HRTEM. These approaches require relatively demanding instrumentation or are not efficient for creating defects on a larger scale.…”
Section: Introductionmentioning
confidence: 99%